2015
DOI: 10.4236/oje.2015.58031
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Mechanisms of Heavy Metal Contaminated Soils: A Review

Abstract: Phytoremediation is a green emerging technology used to remove pollutants from environment components. Mechanisms used to remediate soils contaminated by heavy metal are: phytoextraction, phytostabilisation, phytovolatilization and rhizofiltration. The two first mechanisms are the most reliable. Many factors influence the choice of the suitable phytoremediation strategy for soil decontamination. It depends on soil properties, heavy metal levels and characteristics, plant species and climatic conditions. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 74 publications
1
89
0
10
Order By: Relevance
“…Numerous methods have been used for remediation of heavy metal contaminated soils including thermal desorption, vitrification, soil flushing and solidification/stabilization (Laghlimi et al . ). By burying and diluting the polluted soil with cleaner one, it is possible to remediate the metal contaminated soils making them useful for crop cultivation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous methods have been used for remediation of heavy metal contaminated soils including thermal desorption, vitrification, soil flushing and solidification/stabilization (Laghlimi et al . ). By burying and diluting the polluted soil with cleaner one, it is possible to remediate the metal contaminated soils making them useful for crop cultivation.…”
Section: Introductionmentioning
confidence: 97%
“…At high concentration, it reduces the metabolic processes of plants, including photosynthesis, respiration, cell division, nitrogen metabolism and mineral nutrition (Gallego et al 2012;Rehman et al 2017). Numerous methods have been used for remediation of heavy metal contaminated soils including thermal desorption, vitrification, soil flushing and solidification/stabilization (Laghlimi et al 2015). By burying and diluting the polluted soil with cleaner one, it is possible to remediate the metal contaminated soils making them useful for crop cultivation.…”
mentioning
confidence: 99%
“…But recently phytoremediation, the use of plants to act upon the pollutants, by extracting, degrading or immobilizing them, is gaining momentum, due to its cost-effectiveness, long-term applicability and ecological compatibility (Tangahu et al, 2011;Laghlimi et al, 2015). Among plant species with phytoremediation potential, the halophyte cordgrass Spartina densiflora possesses a high capacity for accumulating heavy metals in its tissues, particularly in roots (Mateos-Naranjo et al, 2008a, 2008b, 2015a, as well as for phytostabilizing them in its rhizosphere (Cambrollé et al, 2008;Redondo-Gómez et al, 2011;Redondo-Gómez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Zn, Cu and Ni are elements that are smoothly absorbed and transported to plant shoots. Finally, Cd has serious negative effects on the plant food chain [71].…”
Section: Assessment Of Trace Elements Accumulated In Tissues Of Phragmentioning
confidence: 99%
“…Although it has been reported that concentrations of metals in below−ground plant tissues are higher than in plant parts located aboveground, it is necessary to consider the biomass of each plant part to evaluate the total accumulation amount [71]. Translocation of accumulated metals in plant tissues could be affected by the interference of several factors such as water pH, microorganism activities as well as plant species and their enzymes [66].…”
Section: Assessment Of Trace Elements Accumulated In Tissues Of Phragmentioning
confidence: 99%